The Effectiveness of Project Based Learning with Performance Assessment on Mathematical Reasoning Ability in View of Self Confidence Students at SMA Negeri 7 Semarang - Marfu'ah, Solikhatun; Masrukan, Masrukan; Walid, Walid (Universitas Mercu Buana Yogyakarta, 2023)
This study aims to test the effectiveness of learning mathematics after applying Project Based Learning (PjBL) with performance assessments on students' mathematical reasoning abilities and analyzing students' mathematical reasoning abilities in terms of self-confidence in PjBL learning with performance assessments. The research method used is a mixed method with a sequential explanatory design. In this study six research subjects were taken based on the level of self-confidence in class X-10 students of SMA Negeri 7 Semarang for the 2022/2023 academic year. The results showed that (1) PjBL learning with an effective performance assessment of students' mathematical reasoning abilities, and (2) research subjects with high self-confidence categories were able to meet all indicators of mathematical reasoning ability to present mathematical statements, make conjectures, manipulate mathematics, draw conclusions , checking the validity of arguments, and finding patterns of mathematical phenomena; subjects in the medium self-confidence category only meet the indicators of presenting mathematical statements, making conjectures, mathematical manipulation; subjects with low self-confidence category only met the indicators of mathematical reasoning ability, namely mathematical manipulation. Recommendations for students with low levels of self-confidence who have not been able to achieve indicators of presenting statements, making conjectures, checking the validity of arguments, and finding patterns of mathematical phenomena by giving assignments independently and doing peer tutoring.